Hypoxia-driven mobilization of altruistic cancer stem cells in platinum-treated head and neck cancer - Pathak, Lekhika; Pal, Bidisha; Talukdar, Joyeeta; Saikia, Partha Jyoti; Sandhya, Sorra; Tasabehji, Wale; Li, Hong; Phukan, Jyotirmoy; Bhuyan, Anjan; Patra, Sanjukta; Das, Bikul (Frontiers in Immunology, 2025)
Circulating tumor cells (CTCs) are under extensive research for their significance in diagnosing cancer metastasis or post-therapy recurrence. CTC may also predict response to chemoradiation. However, its significance in Head and Neck squamous cell carcinoma (HNSCC) progression following chemo radiation is not yet clear. Platinum based chemotherapy plays a key role in managing high-grade HNSCC. We previously reported that tumor hypoxia and or platinum therapy can induce an aggressive tumor stemness defense (TSD) phenotype in the dormant migratory side-population (SPm) fraction of several solid tumor cells lines. We hypothesize that the platinum-induced stress may also induce TSD phenotype in the dormant cancer stem cell (CSC) fraction of HNSCC, which may mobilize to the circulation as CTCs. To test the hypothesis, we followed up 32 subjects of HNSCC in the last five years. Here we report the isolation of EPCAM+/ABCG2+ CTCs with TSD phenotype in the 8/14 subjects with HNSCC receiving platinum-based chemotherapy with or without radiation. These CTCs exhibited hypoxic phenotype, and expressed TSD specific stemness genes. We isolated primary EPCAM+/ABCG2+ cells with TSD phenotype from the surgically resected tumors of 6 HNSCC subjects that underwent platinum based neo-adjuvant therapies. Importantly, when with cisplatin in vitro, these cells exhibited transient expansion and invasion in Boyden Chambers, indicating the CSC niche defense characteristic of the TSD phenotype. Finally, we developed a pre-clinical model of platinum-induced TSD phenotype of SPm fraction of the SCC-25 cell line. The SPm fraction contains EPCAM+/ABCG2+ cells, which expands and mobilize to circulation in the NOD/SCID mice treated with cisplatin. Thus, CTCs in HNSCC exhibit TSD phenotype. Pre-clinical model of chemotherapy induced TSD phenotype could help us to understand the mechanism of the reawakening of dormant EPCAM+/ABCG2+ cells, and their reprogramming to TSD phenotype, and subsequent therapy failure.